Relationship between entrepreneurial leadership practice, school culture and school effectiveness with teacher empowerment in secondary schools of Zamfara State, Nigeria - Dahiru, Abbas Sani (2017)
Previous studies on teacher empowerment argued for strong educational leadership as an antecedent of teacher empowerment in schools. Rarely do studies examine leadership styles such as entrepreneurial leadership practice as a leadership style that enhance teacher empowerment, as well as the effects of school culture and characteristics of effective schools on these relationships, particularly among Secondary schools. Therefore, this study determined the relationship between entrepreneurial leadership, school culture and school effectiveness with teacher empowerment among secondary schools in Zamfara State, Nigeria. The study employed correlational research design, using validated self-administered questionnaires. A total of 395 questionnaires were distributed using Cochran formulae for sample size determination. However, 358 valid responses were returned representing 91 percent. The collected data were analysed using descriptive statistical tools such as percentage, mean and standard deviation, while seven (7) research hypotheses were formulated and tested using inferential statistical tools. Pearson correlation and multiple regression analysis were employed in analysing the data. The descriptive analysis revealed that the levels of all the variables examined in this study were moderate. Based on this result, the researcher concluded that entrepreneurial leadership, school culture, effective schools and teacher empowerment were all significantly related. Furthermore, characteristics of effective schools appeared to be the best predictor of teacher empowerment. Hence, research model confirms the theory that entrepreneurial leadership, school culture and effective schools leads to the actualization of teacher empowerment. Conclusively, these findings can be used by policy makers and administrators to improve their entrepreneurial leadership, school culture and characteristics of effective schools to enhance teacher empowerment among secondary schools in Zamfara State, Nigeria.